PENGARUH PROFITABILITAS, KEPUTUSAN INVESTASI, DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2016) - Sholikhatun Nikmah, 13.05.52.0030; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the factors that affect the firm value that can be judged from its stock price in the stock market. Samples in  this study were 91 manufacturing companies listed on the Indonesia Stock Exchange, which has published a financial report from 2014-2016. Methods of analysis in this study using multiple regression analysis. Testmultiple regression analysis is used to view the simultaneous influence of the profitability, investment decisions, and financing decisions areincluded as independent variables in this study on the firm value. The results showed that variable profitability and investment decisionshave a significant positiveeffect on firm value, while the variable financing decisionshave a significant negative affect on the firm value.Key words: firm value, profitability,  investment decisions,  financing decisions